The Possible Largest Impact Crater in the World: A Case of Central North China - DING Yi (Geography, Earth Science and Environment: Research Highlights Vol. 2, 2024)
Large meteorites pose a threat to lives and would change the course of life evolution on Earth. The three proven large meteorite craters in the world are Vredefort in South Africa, Sudbury in Canada, and Chicxulub in Mexico. This article analyzes some evidence of finding in the northern part of Ordos to propose a possible larger crater than the above. A 325-km long arc-shaped Langshan uplift, a 15 km-deep trench, chaotic strata and numerous thrust layers in the Langshan, abnormal orientation of crystalline basement structures in the north of Ordos, Moho uplift, and meteorite fragments presented in the northern part of the Ordos Basin. All phenomena support a possible meteorite hit event that happened in the northern part of the Ordos Basin during the Late Cretaceous period. The impact pushed the block of the north of Ordos Basin northwestward, subduction after colliding with C P granitoid in the north and forming the trench.